A Hospital Based Prospective Study to Compare Outcome of Osteosynthesis Versus Hemiarthroplasty for the Treatment of Displaced Femoral Neck Fracture - Gurvinder Singh; Atul Singh (International Journal of Health and Clinical Research, 2021)
Background: Cemented Bipolar hemiarthroplasty thus appears a good option for fracture neck femur in the elderly population. With limited evidence for cemented hemiarthroplasty for improved functional outcome and one of the meta-analysis showing increased post-operative mortality. The aim of this study to assess the comparison of functional outcome of osteosynthesis versus hemiarthroplasty for the treatment of displaced femoral neck fracture. Materials & Methods: A hospital based prospective clinical study done on 80 patients involving intracapsular fracture of neck of femur. These patients were randomly divided in two groups; HA group (N=40) and OS group (N=40) selected from Department of Orthopaedic and indoor at our centre Dr Baba Saheb Ambedkar Medical College & Hospital, Rohini, Delhi, India during 2016 to 2019. All patients were operated under General/Spinal anaesthesia for bipolar cemented hemiarthroplasty and internal fixation. The results were classified as excellent, good, fair and poor based on points scored on HARRIS HIP SCORE following functions were taken into consideration. Results: The maximum age of patients was 89 year and minimum age of 50 year with mean age of 74.33 years in HA group & 75.12 yrs in OS group, statistical non-significant (P>0.05). The average hospital stay was 11.27 days in HA group & 12.78 days in OS group, statistical non-significant (P>0.05). They were excellent in 10% patients, 60% patients were having good Harris hip score, 27.5% patients were having fair Harris hip score and only 2.5% patients fell in poor Harris hip score in HA group and in OS group Harris hip score was excellent in 7.5% patients, 50% patients were having good Harris hip score, 35% patients were having fair Harris hip score and only 7.7% patients fell in poor Harris hip score. Conclusion: We concluded that cemented bipolar hemiarthroplasty appears to be an excellent procedure to achieve good clinical results in elderly patients with fracture femoral neck. A continued clinical and radiologically evaluation is essential for identifying complicating factors.